Assessment of Changes in Uterine and Subendometrial Blood Flows By Doppler Sonography in Women Undergoing Assisted Reproduction - Ayşe Figen Türkçapar; Özlem Moraloğlu; Tülin Özdener; Berna Seçkin; Esra Tonguç; Turgut Var; Mustafa Uğur (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: The aim of this study was to evaluate the relationship between uterine Doppler flow and endometrial and subendometrial blood flows and uterine receptivity during ICSI cycles. STUDY DESIGN: A prospective observational study was conducted in sixty-eight women undergoing in-vitro fertilization-embryo transfer (IVF-ET) treatment. All of them had at least one good-quality embryo for transfer on the third day after oocyte retrieval. A color Doppler ultrasound examination was performed on the day of hCG injection and midluteal phase. Pulsatility and resistance index of uterine vessels, and vascularization and endometrial and subendometrial flows were evaluated. RESULTS: The age, duration of infertility or number of embryos transferred of the women who conceived (n=16) and those who did not (n=44) did not statistically significantly differ. The mean endometrial thicknesses of the two groups on hCG day and 5-6days after embryo transfer were not statistically significantly different. The mean uterine arterial resistance index (RI) and Pulsatility Index (PI) values of the two groups were not significantly different on hCG day, but both indices were significantly lower in the pregnant than in the non-pregnant group in mudluteal phase (p=0.05 and 0.016, respectively). In addition, no significant differences were found between the two groups in subendometrial blood flow. CONCLUSION: In patients undergoing IVF-ICSI and embryo transfer, Doppler ultrasound examination of the uterine artery and subendometrial blood flow on hCG day do not discriminate the cycles resulting in conception and non-conception, but especially low mean PI of uterine artery in 5-6 days after ET can predict pregnancy.